Penerapan Behaviorisme dalam Dunia Pendidikan - Naviza Adelia Karisma; Nur faizatul ilmiah; Hermalia Putri Cahya Ramandhani; M. Yunus Abu Bakar (Kampus Akademik Publiser, 2026)
This study entitled “The Application of Behaviorism in the World of Education” aims to examine the implementation of behaviorist learning theory in the learning process, particularly in Arabic language learning. The research was conducted through a literature study by reviewing various books and scientific journals to obtain a comprehensive understanding of the concept of behaviorism. In the field of education, learning theories play an important role in supporting students’ acquisition of knowledge, and one of the widely applied theories is behaviorism. Therefore, this study focuses on the implementation of behaviorist theory in learning practices so that it can be properly understood and effectively applied. Through discussions of the basic concepts, prominent figures, developments, and applications of behaviorist theory, this study is expected to contribute to the improvement and development of more effective learning processes.